1995
DOI: 10.1007/bf02190732
|View full text |Cite
|
Sign up to set email alerts
|

Chidhood precursors of psychiosis as clues to its evolutionary orgins

Abstract: Those who as adults will be admitted to a psychiatric ward with a psychotic illness can be distinguished (on the basis of group differences) from others by their behaviour and academic performance at the ages of 7 and 11 years. Pre-schizophrenic boys are anxious and hostile towards adults and peers at the age of 7 years and show poor concentration. By age 11 years these boys are also rated as depressed, and pre-schizophrenic girls as depressed and withdrawn. Pre-affective psychotic boys show minor changes (for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
116
2
13

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(141 citation statements)
references
References 23 publications
10
116
2
13
Order By: Relevance
“…Crow et al (1995) observed some continuity in academic abilities in pre-schizophrenic children at age 7, 11 and 16 years and Cannon et al (2002) in motor and also other domains between ages 3 and 11. Rosso et al (2000) demonstrated that deviance on motor coordination at age 7 as well as unusual movements at ages 4 and 7 predicted adult schizophrenia.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Crow et al (1995) observed some continuity in academic abilities in pre-schizophrenic children at age 7, 11 and 16 years and Cannon et al (2002) in motor and also other domains between ages 3 and 11. Rosso et al (2000) demonstrated that deviance on motor coordination at age 7 as well as unusual movements at ages 4 and 7 predicted adult schizophrenia.…”
mentioning
confidence: 79%
“…Crow et al (1995) studied the UK 1958 birth cohort where preschizophrenic children at age 7 had been slower to develop continence and had poor coordination and vision; at age 7, 11 and 16 they had poorer academic performance, 4 and at age 16 they were rated as clumsy. Findings consistent with abnormal development of motor co-ordination in the non-academic domain during school years at ages 7 to 11 years have also been reported by Cannon et al (1999) in a large, population-based nested case-control study in Helsinki 1951-1960 well as in a smaller case-control study by Helling et al (2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous retrospective estimates of low premorbid function (e.g., Torrey, Bowler, Taylor, & Gottesman, 1994) and there are recent reports documenting low IQ in a substantial proportion of children and adolescents who later develop schizophrenia (e.g., Cannon et al, 2000Cannon et al, , 2002Khandaker et al, 2011). In addition, large birth cohorts have found that individuals who later develop schizophrenia were often delayed in achieving neuromotor developmental milestones, have premorbid speech abnormalities, and have on average lower levels of educational achievement (Crow, Done, & Sacker, 1995;Poulton et al, 2000, Sorensen et al, 2010. Jones and colleagues (1994) using the 1946 birth cohort, obtained premorbid cognitive scores and found impairments in the educational test scores at ages 8, 11, and 15 of participants who later developed schizophrenia, and this was unrelated to the sex or social class of the subject.…”
Section: Premorbid Intellectual/cognitive Impairmentsmentioning
confidence: 99%
“…Some past epidemiological and clinical reports indicate that this may have resulted from an early developmental problem as evidenced from noted delays in language acquisition and reading abilities (e.g. Crow et al, 1995;DeLisi et al, 1991). Recent fMRI studies provoking activation with a language production paradigm in patients who already have the diagnosis of acute or chronic schizophrenia (Boksman et al, 2005;Kircher et al, 2001Kircher et al, , 2005Koeda et al, 2006;Kubicki et al, 2003;Sommer et al, 2001Sommer et al, , 2003Weiss et al, 2006) and in those during the prodromal stage prior to illness onset and/or at high-genetic risk for illness (Whalley et al, 2004(Whalley et al, , 2005(Whalley et al, , 2006 have shown disruption in the normal lateralized activation in the frontal and temporal cortical circuits for language processing and further evidence that this pattern is heritable (Sommer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%